Acquisition of non-contrastive focus in Russian by adult English-dominant bilinguals - Luchkina, Tatiana; Ionin, Tania; Goldshtein, Maria (Frontiers in Psychology, 2024)
This study investigates the acquisition of sentence focus in Russian by adult English-Russian bilinguals, while paying special attention to the relative contribution of constituent order and prosodic expression. It aims to understand how these factors influence perceived word-level prominence and focus assignment during listening.We present results of two listening tasks designed to examine the influence of pitch cues and constituent order on perceived word prominence (Experiment 1) and focus assignment (Experiment 2) during the auditory comprehension of SV[O]F and OV[S]F sentences in Russian. Our findings reveal an asymmetric pattern: monolingual speakers, as a baseline, tend to perceive the nuclear pitchaccented object as more prominent, particularly in the SVO order, whereas bilinguals appear to be less sensitive to the constituent order distinction.Additionally, baseline speakers consistently assign focus to the sentence-final nuclear pitch-accented noun regardless of constituent order. In contrast, bilinguals demonstrate a preference for assigning focus to the sentence-final nuclear-accented object, rather than the sentence-final nuclear-accented subject. A proficiency effect emerged indicative of a more target-like performance among speakers with greater proficiency in Russian.